Strategi Komunikasi Pembangunan Pariwisata Madura - Syamsul Arifin; Ach. Andiriyanto; Fathurrohman . (PUBLIC CORNER, 2022)
Abstract Madura Island is a unique and interesting island with all the tourism potential it has, such as historical, cultural, religious attractions, natural beauty, including its well-known culinary specialties. However, the magnitude of Madura's tourism potential has not received serious attention from the government, the private sector and the community itself. This study is a conceptual study that provides a new perspective on the communication strategy of Madura tourism development. Some of the concepts of Madura tourism development which are described include the participation of the government as a facilitator and implementer whose role is to make regulations governing the tourism industry, the private sector can play a role in supporting tourism development through funding for development while the community as an actor plays a role in maintaining and maintaining the tourism environment. In realizing participation among the three actors, an open communication system is needed so that through this communication collaboration is built in tourism development. In addition, the Madura tourism development process also needs to be followed by a good promotional strategy in an effort to bring in tourists from outside the island of Madura. Finally, the need for the use of new internet media as a means to introduce Madura tourism widely. Keywords: Madura tourism, development communication, promotion, internet Abstrak Pulau Madura merupakan pulau yang unik dan menarik dengan segala potensi wisata yang dimiliki seperti objek wisata sejarah, budaya, religi, keindahan alam termasuk juga kekhasan kulinernya yang telah dikenal luas. Walaupun demikian, besarnya potensi pariwisata Madura belum mendapat perhatian serius dari pemerintah, pihak swasta dan masyarakat sendiri. Kajian ini sebagai kajian konpseptual yang memberikan pandangan baru tentang strategi komunikasi pembangunan pariwisata Madura. Beberpa konsep pembangunan pariwisata madura yang dijabarkan diantaranya partisipasi pemerintah sebagai fasilitator dan implementator berperan untuk membuat regulasi-regulasi yang mengatur industri pariwisata, sektor swasta dapat berperan mendukung pembangunan pariwisata melalui pendanaan untuk pembangunan sedangkan masyarakat sebagai aktor yang berperan menjaga, dan memelihara lingkungan pariwisata. Dalam mewujudkan partisipasi diantara ketiga aktor tersebut, diperlukan system komunikasi terbuka sehingga melalui komunikasi ini terbangun kolaborasi dalam pembangunan pariwisata. Selain itu proses pembangunan pariwisata madura juga perlu diikuti dengan strategi promosi yang baik dalam upaya mendatangkan wisatawan dari luar pulau madura. Terakhir perlunya pemanfaatan media baru internet sebagai sarana untuk mengenalkan wisata Madura secara luas. Kata Kunci: Pariwisata Madura, komunikasi pembangunan, promosi, internet